A history of modern India - Banerjee-Dube, Ishita (Daryaganj, Delhi, India : Cambridge University Press, 2015)
"Takes up the subject of modern India, tracing developments that have occurred from the eighteenth century to independence"--
The Colourful World of the Eighteenth Century -- Emergence of the Company Raj -- An Inaugural Century -- Creating Anew Proclamations and Promises : The New Imperial Rule -- Imagining India -- Challenge and Rupture -- The Mahatma Phenomenon -- Difficulties and Initiatives -- Many Pathways of a Nation -- The Tumultous Forties -- 1947 and After.
Includes bibliographical references(464-486) and index.
GenEd
Keywords: HISTORY / Asia / India & South Asia; India -- History -- British occupation, 1765-1947.